Karya-Karya Syaikh Abu al-Hasan al-Nadwi: Satu Penilaian - Ahmad, Mohamad Baderudin (Jurnal Usuluddin, 2000)
The article is an attempt to evaluate some of al-Nadwi’s works with a brief introduction on his writing. It gives a short review or an abstract of ten of his selected works.